Electrochemical, ferroelectric and dielectric properties of Gd, Fe and Mn doped nickel perovskite with robust photocatalytic activity under visible light. (15th June 2023) - Ghafoor, Aamir; Bibi, Ismat; Majid, Farzana; Kamal, Shagufta; Jilani, Kashif; Sultan, Misbah; Alwadai, Norah; Ali, Adnan; Ali, Abid; Nazir, Arif; Iqbal, Munawar
Abstract: Single phase La1-x Gd1-x Ni1-2y Fe1-y Mn1-y O3 (x and y = 0.0–0.25) nanomaterials were prepared via microemulsion approach, where effect of dopants on various properties was studied. The slanted rhombohedral phase was formed having particle size in 60–90 nm range. Dielectric parameters value was decreased in lower frequency and constant at higher frequency. The AC conductivity was improved with doping and LNGFM5 (x and y = 0.0–0.25) revealed better current density versus pure LNO. PL analysis suggested that LNGFM5 have improved photocatalytic activity. Thus, higher dielectric constant, AC conductivity and electrochemical properties was enhanced significantly on doping. The optical bandgap was reduced from 2.5 eV (pristine LNO) to 2.0 eV for highly doped material. Doped LNGFM5 catalyst exhibited higher photocatalytic competence by furnishing 92.2% removal of methyl orange (MO) dye in comparison to pristine LaNiO3 (49.5%) within 160 min of irradiation. The catalyst dosage and initial pH of solution significantly affected catalytic activity of LNGFM5. Based on the promising efficiency, the doped LNO materials has ability for the removal of dyes from the wastes under visible light irradiation. Graphical abstract: Image 1